Non-invasive fractional flow reserve (FFRCT) in the evaluation of acute chest pain: concepts and first experiences - Fischer, Andreas; van Assen, Marly; Schoepf, U. Joseph; Matuskowitz, Andrew J.; Varga-Szemes, Akos; Golden, Joseph W.; Giovagnoli, Dante A.; Tesche, Christian; Bayer, Richard R. (European journal of radiology, 2021)
Objective - To evaluate 30 day rate of major adverse cardiac events (MACE) utilizing cCTA and FFRCT for evaluation of patients presenting to the Emergency Department (ED) with acute chest pain. - Materials and methods - Patients between the ages of 18-95 years who underwent clinically indicated cCTA and FFRCT in the evaluation of acute chest pain in the emergency department were retrospectively evaluated for 30 day MACE, repeat presentation/admission for chest pain, revascularization, and additional testing. - Results - A total of 59 patients underwent CCTA and subsequent FFRCT for the evaluation of acute chest pain in the ED over the enrollment period. 32 out of 59 patients (54 %) had negative FFRCT (>0.80) out of whom 18 patients (55 %) were discharged from the ED. Out of the 32 patients without functionally significant CAD by FFRCT, 32 patients (100 %) underwent no revascularization and 32 patients (100 %) had no MACE at the 30-day follow-up period. - Conclusion - In this limited retrospective study, patients presenting to the ED with acute chest pain and with CCTA with subsequent FFRCT of >0.8 had no MACE at 30 days; however, for many of these patients results were not available at time of clinical decision making by the ED physician.